1987
DOI: 10.1002/jat.2550070605
|View full text |Cite
|
Sign up to set email alerts
|

Hepatotoxicity induced by the herbicide atrazine in the rat

Abstract: The hepatotoxicity of atrazine was investigated by studying clinical parameters related to hepatic function and by electron microscopy. Three groups to male albino rats (Wistar strain) received 100, 200 and 400 mg of atrazine/per kg of body weight/per day, for 14 days. One group received 600 mg atrazine/per kg of body weight/per day, for 7 days. At termination of dosing, the animals were sacrificed and blood was drawn for the determination of serum total lipids, glucose, alanine aminotransferase (ALT) and alka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(15 citation statements)
references
References 9 publications
2
13
0
Order By: Relevance
“…10,53 Previous reports have shown that ATR causes cellular morphological changes and induces irregular shapes in subcellular organelle such as the ER. 54 In this study, the ultrastructural analysis shows ER injury. This is in accordance with previous studies in common carp gills induced by ATR exposure.…”
Section: Discussionmentioning
confidence: 62%
“…10,53 Previous reports have shown that ATR causes cellular morphological changes and induces irregular shapes in subcellular organelle such as the ER. 54 In this study, the ultrastructural analysis shows ER injury. This is in accordance with previous studies in common carp gills induced by ATR exposure.…”
Section: Discussionmentioning
confidence: 62%
“…[1345] It is also possible that the slight degeneration of hepatocytes in the ATZ-treated rats and/or mild periportal cellular infiltration by mononuclear cells in the ATZ + Q5-treated rats were sufficient to induce the release of the serum markers from the liver into the systemic circulation which was completely prevented on co-administration of Q10. The susceptibility of renal tissues to the toxic effects of noxious chemicals can be attributed in part to the differences in the anatomic and physiologic features of this organ.…”
Section: Resultsmentioning
confidence: 99%
“…[12] It is known to cause hepatic damage in rats and pigs;[131415] disrupt the functioning of the reproductive tissues;[161718] cause DNA damage and genotoxicity in the stomach, kidney, and liver of rats;[1920] damage rat erythrocytes[21] as well as induce oxidative stress in several experimental models. [8212223] We previously reported that ATZ at a dose of 120 mg/kg induces oxidative stress in rat tissues and blood at 16 days of treatment, and that the oxidative stress was associated with increased lipid peroxidation and changes in the antioxidative system.…”
Section: Introductionmentioning
confidence: 99%
“…Liver is viewed as a primary organ for atrazine metabolism, which is known to cause hepatic damage in mammalian [15, 43, 44]. However, whether the effects of atrazine have the potential influence to the cardiac and hepatic function of birds still remain unclear.…”
Section: Discussionmentioning
confidence: 99%